Light-Emitting Diode Laser Therapy for HyperoxiaInduced Retinal Abnormalities: LED Laser Therapy for Retinal Hyperoxia - Abd Eldaiem, Maha Sabry; Abdelkawi, Salwa Ahmed; Elsaeid, Aziza Abdelmonem; Hassan, Aziza Ahmed; Ghoneim, Dina fouad; El Rashedi, Ahlam Ibrahim (Journal of Lasers in Medical Sciences, 2021)
Introduction: Hyperoxygenation is linked to numerous effects in a variety of organ systems. It can cause tissue damage by generating reactive oxygen species (ROS), increasing oxidative stress, and inducing cell death by apoptosis. The present study aimed to evaluate the effects of low-level laser therapy on the retina in response to acute hyperoxia in animals. Methods: A total of 70 Wistar albino rats were evaluated in the present study: 10 rats were designated as a control group, and the rest were exposed to hyperoxia (O2, 90%) for 3 days, 1 week, and 2 weeks (20 rats each). Each group was divided into two subgroups (n=10), one of which was designated as hyperoxia only. The other was treated with a 670 nm light-emitting diode laser (2 sessions/one week, 9.0 J/cm2) in each eye. The animals were euthanized, and their retinas were dissected for analysis of protein content, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), total antioxidant capacity (TAC), hydrogen peroxide (H2O2), malondialdehyde (MDA), and histological examination. Results: We found that two weeks of hyperoxia-induced an increase in retinal protein content (P<0.001), an alteration in the intensities and molecular weights of protein fractions, a significant decrease in the TAC level (P<0.01), and a noticeable increase in H2 O2 and MDA levels (P<0.001). Histological examination revealed fragmentation of the photoreceptors and neovascularization in the outer and inner plexiform layers. Furthermore, the data showed remarkable improvement in the retinal protein contents, oxidative state, and retinal structure after light-emitting diode laser therapy. Conclusion: Light-emitting diode laser therapy was found to be a useful treatment paradigm for reducing hyperoxia-induced retinal damage. DOI: 10.34172/jlms.2021.64